CONTENT OF USING INFORMATION TECHNOLOGIES IN EDUCATION - Saidova Mohinur Jonpolatovna; Mexmonova Sitora Imomovna (Scholar Express Journal, 2023)
This article provides information on the requirements for a modern teacher, on the special qualities that he must possess, on the role of the information society and the educational process. Provides details on important information and telecommunication technologies used in education
Keywords: informatization; education; science; personality development